2018
DOI: 10.1186/s13756-018-0328-y
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobials in small-scale urban pig farming in a lower middle-income country – arbitrary use and high resistance levels

Abstract: BackgroundAdministration of antimicrobials to food-producing animals is regarded as a major contributor to the overall emergence of resistance in bacteria worldwide. However, few data are available on global antimicrobial use and resistance (AMR) in livestock, especially from low- and middle-income countries.MethodsWe conducted a structured survey of 91 small-scale pig farms in the urban and peri-urban areas of Phnom Penh, Cambodia, to assess the farmers’ knowledge, attitudes and practices related to antimicro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
1
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 35 publications
(40 reference statements)
3
59
1
8
Order By: Relevance
“…Pigs were often kept in crowded confinement (Osbjer et al, ), which allows for frequent transmission of bacteria. Previous studies have found that antibiotic use in the pig and poultry industry in Cambodia is widespread and uncontrolled (Om & McLaws, ; Ström, Boqvist, et al, ). ESCE is also frequent in poultry production in Europe, even in countries with low antibiotic resistance burden, and the prevalence is mainly related to vertical transmission (Blaak et al, ; Borjesson et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pigs were often kept in crowded confinement (Osbjer et al, ), which allows for frequent transmission of bacteria. Previous studies have found that antibiotic use in the pig and poultry industry in Cambodia is widespread and uncontrolled (Om & McLaws, ; Ström, Boqvist, et al, ). ESCE is also frequent in poultry production in Europe, even in countries with low antibiotic resistance burden, and the prevalence is mainly related to vertical transmission (Blaak et al, ; Borjesson et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A study on backyard chicken farms in Vietnam concluded that detection of mcr‐1 ‐carrying bacteria in chicken samples was associated with colistin use and that detection in human samples was associated with exposure to mcr‐1 ‐positive chickens (Trung et al, ). Through interviewing pig farmers in Cambodia, Ström, Boqvist, et al ()) found that antibiotic use, including colistin, was common in pig farms and sometimes used as prophylactic treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately half of these colonization isolates had MLSTs detected among food, and a substantial portion were more likely to produce CTX-M-55 and be amphenicol resistant than colonization isolates that grouped separately. The fact that chloramphenicol has not been used in human medicine for almost 20 years in Cambodia, yet chloramphenicol analogs (e.g., florfenicol, thiamphenicol) are administered to food animals ( 5 , 7 ), suggests a food origin for these colonizing isolates.…”
Section: The Studymentioning
confidence: 99%
“…High ESBL colonization rates in low- and middle-income countries such as Cambodia are usually attributed to unrestricted consumer access to and hospital overuse of third-generation cephalosporins ( 3 , 4 ). However, antimicrobial drugs in classes critical for human health (e.g., β-lactams, macrolides, aminoglycosides, polymyxins) are increasingly being used in food animals ( 5 ). In Cambodia, weak public health protections and consumption of undercooked animal products could exacerbate the spread of ESBL-producing E. coli or ESBL genes from animals to humans.…”
mentioning
confidence: 99%